Computational Analyses of Amino Acid Molecules in PDE7A for Elucidating their Evolutionary Diversity and Protein Interactions in Multiple Mammalian Species - Narjes El Osta; Zainab El Mabrouk; Omran Algriany (AlQalam Journal of Medical and Applied Sciences, 2024)
This study explores the protein interactions and evolutionary conservation of phosphodiesterase type 7A (PDE7A) across different species, to identify the species with the highest similarity to humans, which has important applications in many fields such as pharmacology, comparative biology, biochemistry, oncology, endocrinology, and reproductive sciences. Computational analyses of the amino acid sequence of this enzyme revealed a common evolutionary relationship between the selected species and humans, but camels show the most variable evolutionary lineage in their PDE7A protein over time. In searches for homologous proteins, identity analysis results for four returned amino acid sequences were as follows: 91.81 ± 4.25% (mean ± SD), while the similarity between the sequences was 94.66% ± 4.55, and analysis of BLOSUM62 (Blocks Substitution Matrix 62) yielded a minimum value of 0.901 ± 0.055. All species have closely related physicochemical properties. The computational analyses revealed conserved amino acid residues of the gene across the studied species, which likely contribute to the similar expression patterns of the PDE7A gene in various animals. The findings also suggest that rats are a suitable model for gaining deeper insights into human biology. تستكشف هذه الدراسة التفاعلات البروتينية والحفظ التطوري لإنزيم فوسفوديستيريز النوع اي 7 عبر الأنواع المختلفة، بهدف تحديد الأنواع ذات أعلى قدر من التشابه مع البشر، وهو ما له تطبيقات مهمة في العديد من المجالات مثل علم الأدوية، علم الأحياء المقارن، الكيمياء الحيوية، علم الأورام، الغدد الصماء، وعلوم الإنجاب. كشفت التحليلات الحسابية لتسلسل الأحماض الأمينية لهذا الإنزيم عن علاقة تطورية مشتركة بين الأنواع المختارة والبشر، لكن الجمال تظهر السلالة التطورية الأكثر تنوعًا في بروتين فوسفوديستيريز النوع اي 7 بمرور الوقت. في عمليات البحث عن البروتينات المتجانسة، كانت نتائج تحليل الهوية لأربعة تسلسلات من الأحماض الأمينية المسترجعة على النحو التالي: 91.81 ± 4.25% (متوسط ± انحراف معياري)، بينما كان التشابه بين التسلسلات 94.66% ± 4.55، وأسفر تحليل BLOSUM62 (مصفوفة استبدال الكتل 62) عن قيمة دنيا تبلغ 0.901 ± 0.055. جميع الأنواع لها خصائص فيزيوكيميائية وثيقة الصلة. كشفت التحليلات الحسابية عن بقايا أحماض أمينية محفوظة للجين عبر الأنواع المدروسة، والتي من المحتمل أن تساهم في أنماط التعبير المتشابهة لجين فوسفوديستيريز النوع اي 7 في حيوانات مختلفة. تشير النتائج أيضًا إلى أن الجرذان نموذج مناسب لاكتساب رؤى أعمق في علم الأحياء البشري.